PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MINAT BELAJAR DAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Sunita, Ni Wayan; Mahendra, Eka; Lesdyantari, Eka (LP2M IKIP PGRI Bali, 2019)
The main purpose of this research was to find out the presence of the influence of project based learning model against the interest learn and learning results mathematics on students  grade VIII Smp Dharma Wiweka Denpasar in the academic year of  2017/2018.           The type of research that was used was quasi eksperiment and the design of the research used the non equivalen posttest only control grup design. The population in this study were all students of class VIII of Dharma Wiweka Denpasar junior high school by 9 classes involving 2 class samples taken by using simple random sampling technique. The nstrument of the research that was used to gather the data was questionnaire of interest learn and learning results mathematics. the next data was analyzed using the MANOVA test  with SPSS 23.0 for Windows test with score of Sig. 0,000 < 0,05.            The results of the analysis showed that : (1) there were differences in linterest learn between the students that followed the learning model of  Project Based Learning with students  that followed  the conventional learning model of grade VIII at SMP Dharma Wiweka Denpasar. It could be seen from the result of the MANOVA, (2) there were differences in the learning result mathematics between the students that followed the learning model of  Project Based Learning with students  that followed  the conventional learning model of grade VIII at SMP Dharma Wiweka Denpasar. It could be seen from the result of the MANOVA, and (3) there is a simultaneous difference of learning interest and learning results mathematics between the students that followed the learning model of  Project Based Learning with students  that followed  the conventional learning model of grade VIII at SMP Dharma Wiweka Denpasar. It could be seen from the result of the MANOVA.So there are an effect from the learning model of Project Based Learning contain towards the student?s mathematics learning interest and result.